Calibration procedures for the quantitative determination of membrane potential in human cells using anionic dyes. Issue 7 (6th May 2013) - Klapperstück, Thomas; Glanz, Dagobert; Hanitsch, Stefan; Klapperstück, Manuela; Markwardt, Fritz; Wohlrab, Johannes
Abstract : Quantitative determinations of the cell membrane potential of lymphocytes (Wilson et al., J Cell Physiol 1985;125:72–81) and thymocytes (Krasznai et al., J Photochem Photobiol B 1995;28:93–99) using the anionic dye DiBAC4 (3) proved that dye depletion in the extracellular medium as a result of cellular uptake can be negligible over a wide range of cell densities. In contrast, most flow cytometric studies have not verified this condition but rather assumed it from the start. Consequently, the initially prepared extracellular dye concentration has usually been used for the calculation of the Nernst potential of the dye. In this study, however, external dye depletion could be observed in both large IGR‐1 and small LCL‐HO cells under experimental conditions, which have often been applied routinely in spectrofluorimetry and flow cytometry. The maximum cell density at which dye depletion could be virtually avoided was dependent on cell size and membrane potential and definitely needed to be taken into account to ensure reliable results. In addition, accepted calibration procedures based on the partition of sodium and potassium (Goldman‐Hodgkin‐Katz equation) or potassium alone (Nernst equation) were performed by flow cytometry on cell suspensions with an appropriately low cell density. The observed extensive lack of concordance between the correspondingly calculated membrane potential and the equilibrium potential of DiBAC4 (3) revealed that these methods require the additional measurement of cation parameters (membrane permeability and/or intracellular concentration). In contrast, due to the linear relation between fluorescence and low DiBAC4 (3) concentrations, the Nernst potential of the dye for totally depolarized cells can be reliably used for calibration with an essentially lower effort and expense. © 2013 International Society for Advancement of Cytometry